A 'Hydrolase Switch' for Vascular Specialization in Plant Pathogenic Bacteria. (May 2021) - Redkar, Amey; Sabale, Mugdha; Di Pietro, Antonio
Abstract : Plant vascular diseases are tissue-specific systemic infections provoked by bacterial and fungal pathogens adapted to thrive in the xylem vessels. A recent report by Gluck-Thaler et al . reveals that, in the phytopathogenic bacterium Xanthomonas, the switch from non-vascular to vascular pathogenesis is determined by a single gene encoding a plant cell wall-degrading hydrolase.